Etablering og strukturering af database til generering af tre elektroniske monofunktionelle ”phrasal verb” ordbøger - Andersen, Birger (Nordiske Studier i Leksikografi, 2010)
The motivation for creating a database for the generation of monofunctional English phrasal verb dictionaries lies first and foremost in the semantic opaqueness of many English phrasal verbs, which gives rise to reception and translation difficulties. Secondly, even students whose mother tongue has structures similar to English phrasal verbs have production problems, especially because of uncertainty with respect to formality levels of individual phrasal verbs. On the basis of the functional theory of lexicography, the article describes the structure and contents of a database for the generation of three monofunctional English phrasal verb dictionaries (for reception, production and translation into Danish) and discusses the issue of which sets of data in the database to include in each of the three monofunctional dictionaries.